Sappia-Christ, The Rice of Life: Re-imagining Christ based on the Story of a Breastfeeding Goddess - Sanchez, Rachel Joyce Marie O (Archīum Ateneo, 2019)
The importance of rice as the staple food in the Philippines; the reality of poverty and hunger that affect many Filipino women and their families and Muriel Orevillo-Montenegro's challenge in "The Jesus of Asian Women" (2006) to Philippine feminist theologians to consider female images of Christ serve as the background of this paper. In the context of the importance of rice in Philippine society and in response to hunger experienced in an urban poor community; women of a particular parish initiate and observe "Isang Dakot ng Bigas" (One Handful of Rice) in Basic Ecclesial Communities (BEC); a practice wherein members of BECs contribute rice grains for members of the community in dire need. This turns out to have life-giving effects for the BEC and its active members' neighbors. The significance of rice is reflected in many myths in the Philippines. One of these myths is a narrative about the origin of rice from Bohol. It that tells of a goddess who; moved by compassion for the poor; selects what used to be an insignificant weed; and squeezes both her breasts upon it for milk until even blood comes out in order to make rice grains. This goddess is explored as a Christ-figure by bringing out Christological themes from her story; such as sacrifice; compassion for the poor; and faith. When this Christological image is viewed in the context of the experiences of women involved in "Isang Dakot ng Bigas" it can be seen as liberating; but it must also be taken with a grain of salt. The image of a sacrificing mother that emerges from the myth may lead to further enslavement for women. However; instead of giving until it hurts"; the women of the BEC show that sharing can be done by everyone creatively..."